4-Ethylguaiacol Modulates Neuroinflammation and Promotes Heme Oxygenase-1 Expression to Ameliorate Brain Injury in Ischemic Stroke - Weng, Wen-Tsan; Kuo, Ping-Chang; Scofield, Barbara A.; Paraiso, Hallel C.; Brown, Dennis A.; Yu, I-Chen; Yen, Jui-Hung (Frontiers in Immunology, 2022)
Ischemic stroke is caused by a sudden reduction in cerebral blood flow that subsequently induces a complex cascade of pathophysiological responses, leading to brain inflammation and irreversible infarction. 4-ethylguaiacol (4-EG) is reported to suppress inflammatory immune responses. However, whether 4-EG exerts anti-inflammatory effects in ischemic stroke remains unexplored. We evaluated the therapeutic potential of 4-EG and examined the cellular and molecular mechanisms underlying the protective effects of 4-EG in ischemic stroke. The effect of 4-EG in ischemic stroke was determined by using a transient middle cerebral artery occlusion (MCAO) animal model followed by exploring the infarct size, neurological deficits, microglia activation, inflammatory cytokine production, blood–brain barrier (BBB) disruption, brain endothelial cell adhesion molecule expression, and microglial heme oxygenase-1 (HO-1) expression. Nrf2-/- and HO-1 inhibitor ZnPP-treated mice were also subjected to MCAO to evaluate the role of the Nrf2/HO-1 pathway in 4-EG-mediated protection in ischemic stroke. We found that 4-EG attenuated infarct size and neurological deficits, and lessened BBB disruption in ischemic stroke. Further investigation revealed that 4-EG suppressed microglial activation, peripheral inflammatory immune cell infiltration, and brain endothelial cell adhesion molecule upregulation in the ischemic brain. Finally, we identified that the protective effect of 4-EG in ischemic stroke was abolished in Nrf2-/– and ZnPP-treated MCAO mice. Our results identified that 4-EG confers protection against ischemic stroke and reveal that the protective effect of 4-EG in ischemic stroke is mediated through the induction of the Nrf2/HO1 pathway. Thus, our findings suggest that 4-EG could be developed as a novel therapeutic agent for the treatment of ischemic stroke.